2022
DOI: 10.1097/jnn.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in Stroke Nursing Research: Global Views From a Panel of Nurse Researchers

Abstract: INTRODUCTION: A diverse group of neuroscience nurse experts discussed stroke nursing research at the 5th International Neuroscience Nursing Research Symposium. Panel experts from Singapore, India, Australia, New Zealand, the Philippines, Malawi, Germany, Palestine, Kenya, Japan, and the United States collaborated to examine similarities and differences in nurse-led stroke research conducted in their home countries. This article reflects panel insights on challenges and opportunities for nurse-led stroke resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Through scholarship of practice, neuroscience nurses can inform and impact nursing practice on a global level. 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through scholarship of practice, neuroscience nurses can inform and impact nursing practice on a global level. 27…”
Section: Discussionmentioning
confidence: 99%
“…Through scholarship of practice, neuroscience nurses can inform and impact nursing practice on a global level. 27 There are opportunities for neuroscience nurses to render first-line defense for both patients with neurological conditions and their family through interventions aimed to promote resilience, decrease burden, and enhance coping and knowledge. Establishment of coordinated care services through shared decision making with patients, family caregivers, and nurses is pivotal to minimize caregiver strain.…”
Section: Discussionmentioning
confidence: 99%
“…When these are lacking, the effectiveness of nursing care, the design of interventions, and the scope of nursing research are adversely affected. 26 Career advancement, recruitment, and retention may be negatively affected as well. 16 ItÕs increasingly common for students to browse the internet and social media platforms as they consider career paths.…”
Section: Discussionmentioning
confidence: 99%
“…But diversity and inclusivity should be nonnegotiable in all professional environments. When these are lacking, the effectiveness of nursing care, the design of interventions, and the scope of nursing research are adversely affected 26. Career advancement, recruitment, and retention may be negatively affected as well 16…”
Section: Discussionmentioning
confidence: 99%
“…It is considered that the performance of nursing interventions such as "immobility management", "activity and exercise", and "physical comfort promotion" in order to solve the limitation of body movement due to paralysis and the immobility, subluxation, genu recurvate, and muscular weakness problem was high due to the characteristics of patients with stroke. In previous studies related to the nursing process with stroke, physical mobility was identified as a priority nursing problem and diagnosis [21]. This is justified by the result that stroke is a neurogenic motor disease likely leading to damage of voluntary movement control.…”
Section: Nursing Interventions For Stroke Patientsmentioning
confidence: 99%